Aloysius taught himself Gaelic and botany, reported by The Newfoundland Herald - Mannion,Maura (1982)
Aloysius was not only a farmer, as an Irish descendant, he also learnt Gaelic by himself through books and tapes. Further, he was a self-taught botanist and studied numerous books on the subject.